Brain 5-HT Deficiency Prevents Antidepressant-Like Effects of High-Fat-Diet and Blocks High-Fat-Diet-Induced GSK3β Phosphorylation in the Hippocampus - Karth, Michelle M.; Baugher, Brittany J.; Daly, Nicole; Karth, Melinda D.; Gironda, Stephen C.; Sachs, Benjamin D. (Frontiers in Molecular Neuroscience, 2019)
Obesity is associated with an increased risk of depression and anxiety disorders, but the nature of the relationship(s) between obesity and mental illness remain highly controversial. Some argue that depression and/or anxiety lead to increased consumption of ‘comfort foods,’ the intake of which reduces negative affect and promotes obesity. In contrast, others have theorized that negative affect results from chronic excessive consumption of highly palatable foods. The brain serotonin (5-HT) system has long been implicated in both the development and treatment of mental illness. Preclinical studies have shown that low brain 5-HT exacerbates depression- and anxiety-like behavior induced by stress and blocks reductions in depression-like behavior induced by antidepressants, but the effects of brain 5-HT deficiency on responses to high fat diet (HFD) have not been explored. The current work used genetically modified mice to evaluate the effects of low 5-HT on behavioral and molecular alterations induced by chronic exposure to HFD. Our results reveal that HFD decreases depression-like behavior and increases some anxiety-like behaviors in wild-type (WT) mice. However, genetic brain 5-HT deficiency blocks HFD-induced reductions in forced swim immobility and prevents HFD-induced increases in hippocampal GSK3β phosphorylation despite having no significant effects on HFD-induced changes in body weight or anxiety-like behavior. Together, our results suggest that brain 5-HT deficiency significantly impacts a subset of behavioral and molecular responses to HFD, a finding that could help explain the complex relationships between obesity and mental illness.